2015
DOI: 10.1002/2014wr016254
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive, multiobjective optimal sequencing approach for urban water supply augmentation under deep uncertainty

Abstract: Optimal long-term sequencing and scheduling play an important role in many water resources problems. The optimal sequencing of urban water supply augmentation options is one example of this. In this paper, an adaptive, multiobjective optimal sequencing approach for urban water supply augmentation under deep uncertainty is introduced. As part of the approach, optimal long-term sequence plans are updated at regular intervals and trade-offs between the robustness and flexibility of the solutions that have to be f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 61 publications
0
73
0
Order By: Relevance
“…Examples of the application of RO in the development of long-term water management strategies can be found in Kwakkel et al (2014), Giuliani et al (2014), Herman et al (2014), Kang and Lansey (2013) and Beh et al (2015b) and for adaptive policymaking in Hamarat et al (2012). Within this research it was found that RO could handle complex, deeply uncertain problems with large numbers of possible solutions.…”
Section: The Current Approach Within the Uk As Stated In The Environmentioning
confidence: 87%
See 2 more Smart Citations
“…Examples of the application of RO in the development of long-term water management strategies can be found in Kwakkel et al (2014), Giuliani et al (2014), Herman et al (2014), Kang and Lansey (2013) and Beh et al (2015b) and for adaptive policymaking in Hamarat et al (2012). Within this research it was found that RO could handle complex, deeply uncertain problems with large numbers of possible solutions.…”
Section: The Current Approach Within the Uk As Stated In The Environmentioning
confidence: 87%
“…percentage) of future supply and demand scenarios that result in an acceptable system performance (Paton et al 2014a;Beh et al 2015b), i.e. as follows:…”
Section: Robustness Of Water Supplymentioning
confidence: 99%
See 1 more Smart Citation
“…Paton et al (2014) developed a framework for water supply system planning with alternative sources and climate change considerations, while Beh et al (2014Beh et al ( , 2015 developed two methods for optimal sequencing of urban water supply augmentation options under deep uncertainty regarding demands and climate. The research by both Paton et al (2014) and Beh et al (2014Beh et al ( , 2015 considered only the planning of water supply projects, and did not optimize the specific design or operation of the systems. Sequencing is also considered in Cai et al (2015), however, in this case it is applied to planning of drought mitigation strategies in agricultural systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within the current climate, there may be multiple realizations of possible rainfall and streamflow series (for example dry or wet years). Beh et al (2015) considered rainfall, as well as population and temperature, as uncertain variables in their optimal sequencing methodology for water supply system augmentation. They considered both climate and hydrologic variability: seven possible future climate scenarios provided different forecasted rainfall reductions, and within each of these seven scenarios, 20 stochastic replicates of the rainfall sequence were produced.…”
Section: Rainfall and Streamflowmentioning
confidence: 99%